2016
DOI: 10.1016/j.msard.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica relapses: Race and rate, immunosuppression and impairment

Abstract: Relapse rates in NMO are influenced by multiple factors, including age, ethnicity and disease duration. Current immunosuppressive treatments reduce but do not abolish relapses, however, they appear to additionally lessen the chronic disabling effect of a relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 14 publications
4
27
0
1
Order By: Relevance
“…Similar to previous studies [ 3 10 ], MMF therapy significantly reduced ARR in 87% of patients, and 64% were relapse-free during a median course of 20 months (average 27) therapy with MMF. Our results confirmed that MMF therapy significantly decreased the risks of severe relapses, in terms of disability, as recently reported [ 9 , 10 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies [ 3 10 ], MMF therapy significantly reduced ARR in 87% of patients, and 64% were relapse-free during a median course of 20 months (average 27) therapy with MMF. Our results confirmed that MMF therapy significantly decreased the risks of severe relapses, in terms of disability, as recently reported [ 9 , 10 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Treatment was changed from AZA to RTX in eight patients. This could have generated a bias in favour of a low ARR in the AZA subgroup, as patients who responded well to the treatment might have remained on therapy more often as reported in another cohort; 31 in addition, patients with a high ARR under AZA treatment might have been switched to RTX. Moreover, we cannot completely exclude that patients with more aggressive disease were more commonly treated with RTX than AZA based on the presumption of treatment superiority.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that certain races, specifically Afro-Caribbeans, have greater relapse rates [17]. This may drive providers to treat non-Caucasian patients more aggressively and favor first-line rituximab in this patient population.…”
Section: Discussionmentioning
confidence: 99%